Hyperthyroidism With Atrial Fibrillation in Children: A Case Report and Review of the Literature - Subramonian, Deepa; Wu, Yuwei Juliana; Amed, Shazhan; Sanatani, Shubhayan (Frontiers in Endocrinology, 2021)
Atrial fibrillation is exceedingly rare in children with structurally and functionally normal hearts. We present a novel case of a 15-year-old female with known hyperthyroidism who subsequently developed atrial fibrillation. She had been suffering from fatigue, heat intolerance and myalgias for 6 months. Her initial TSH was 0.01mU/L, and free T4 was 75.4 pmol/L, with a free T3 of >30.8 pmol/L. An electrocardiogram showed atrial fibrillation with a ventricular rate of 141 beats per minute. An echocardiogram demonstrated an enlarged left atrium and ventricle, with mild mitral regurgitation. She was treated with methimazole and underwent synchronized cardioversion. She subsequently returned to a euthyroid state and remained in normal sinus rhythm. In this case, we discuss the physiologic and arrhythmogenic properties of thyroid hormone, with a summary of the existing literature on atrial fibrillation in hyperthyroidism in children. Current guidelines for treatment of atrial fibrillation are also outlined.